Trading Friction and Spread Decomposition in Indonesian Stock Exchange - Nurhayati, Immas; Ekaputra, Irwan Adi; Husodo, Zäafri Ananto (UI Scholars Hub, 2018)
We examine the intraday trading and price change for frequently traded stocks in Indonesian Stock Exchange. Using bid and ask price, trade price, number of trade, trade volume, we estimate trading friction and spread decomposition. The objective of the estimation is to infer what is the biggest component of trading friction. The result of 50 most frequently traded stocks in the Indonesian Stock Exchange using trading friction estimator conclude that the average trading friction of high market capitalization and the most relatively liquid stocks, scattered in various fractions price is equal to 1% per year, and the highest trading frictions derived from the information and it is consistent with spread decomposition estimator.